Book Reviews. Issue 1 (1st June 2022) - Unknown
Abstract : William A. Galston, Anti-Pluralism: The Populist Threat to Liberal Democracy (New Haven, CT: Yale University Press, 2018) Gergana Dimova, Democracy Beyond Elections: Government Accountability in the Media Age (London: Palgrave Macmillan, 2020) David Stasavage, The Decline and Rise of Democracy: A Global History from Antiquity to Today (Princeton, NJ: Princeton University Press, 2020) G. John Ikenberry, A World Safe for Democracy: Liberal Internationalism and the Crises of Global Order (New Haven, CT: Yale University Press, 2020) Cristina Lafont, Democracy without Shortcuts: A Participatory Conception of Deliberative Democracy (Oxford: Oxford University Press, 2020)